Mentoring first-time and low-level delinquent adolescents: the impact of an on-campus mentoring program on sense of self and rule non-compliance - Leboeuf, Jordan Lindsay, author; Haddock, Shelley, committee member; Zimmerman, Toni, committee member; Henry, Kim, committee member (Colorado State University. Libraries, 2011)
Researchers have linked sense of self variables such as self-esteem and self-concept to delinquent activity among adolescents for decades, finding that delinquency is often associated with lower levels of sense of self and proposing that lower self-esteem may motivate delinquent behavior. This thesis first considers relevant research and theories, and then presents an evaluation of Campus Corps, a college-campus mentoring program for low-level or first-time offending youth. Using hierarchical regression models, it was determined that youth in Campus Corps, compared to non-participants, experienced higher levels of self-esteem, self-concept, and feelings of being important to others. Youth in higher-quality mentor relationships experienced, on average, lower rule non-compliance, higher self-esteem, higher feelings of being noticed by others, and higher feelings of being important to others. This program evaluation contributes to the small body of research on mentoring programs for delinquent and status-offending youth, adding to the definition of what makes a mentoring program effective.
Keywords: mentor; adolescents; delinquency; self-esteem; mattering